Dark shamans : kanaimà and the poetics of violent death - Whitehead, Neil L. (e-Duke books scholarly collection., 2002)
Uses an ethnographic example of ritual violence to illuminate cultural expression more widely and thereby reformulate anthropological and historical approaches to warfare and violence.